2002
DOI: 10.1186/1472-6920-2-3
|View full text |Cite
|
Sign up to set email alerts
|

Geographical distribution of publications in the field of medical education

Abstract: Background: The geographical distribution of publications as an indicator of the research productivity of individual countries, regions or institutions has become a field of interest. We investigated the geographical distribution of contributions to the two leading journals in the field of medical education, Academic Medicine and Medical Education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 21 publications
2
55
0
1
Order By: Relevance
“…The limited number of reported research projects in medical education from sub-Saharan African countries has been documented before. [15][16][17] This review confirms the previous observation and confirms the discrepancy in literature relating to research on WBA among interns.…”
Section: Discussionsupporting
confidence: 79%
“…The limited number of reported research projects in medical education from sub-Saharan African countries has been documented before. [15][16][17] This review confirms the previous observation and confirms the discrepancy in literature relating to research on WBA among interns.…”
Section: Discussionsupporting
confidence: 79%
“…Tutarel (2002) showed that the Netherlands appears among the five most productive countries when it comes to publications in two leading medical education journals between 1995 and 2000. Recently, a survey of the 2006 volumes of 9 medical education journals was conducted, which counted the number of articles with a first author from these same five countries.…”
Section: Research and Development Of Dutch Medical Educationmentioning
confidence: 99%
“…Because the affiliation field in MEDLINE was also searchable, a lot of bibliometric researches took advantage of this new function to analyze the national output in biomedicine. [7][8][9][10][11] In our current study, we went a step further to extract a specific specialty of a nation from the affiliation field. Such an approach was feasible only when the data existed and the designation of institutions did not vary too much.…”
Section: Discussionmentioning
confidence: 99%